Fitness profile of young elite basketball players (Cadets) - Sporis, G.; Naglic, V.; Milanovic, L.; Talovic, M.; Jeleskovic, E. (Acta Kinesiologica, 2010)
The purpose of this study was to evaluate weather players in different positional roles have a different physical and physiologic profile. Also to determine weather is a connection or differences in the motor tests and situation efficiency. Secondary goal was to determine differences between initial, transitive and final test results through preparation period. For the purpose of this study, measurements were taken on 12 best players of Croatia national team under 16 years (born 1993. and younger). According to the positional roles, players were categorized as 1 - point guard (n=2), 2 - shooting guard (n=4), 3 - small forward (n=2), 4 - forward (n=3) i 5 - center (n=1). They were tested with 9 variables (internship, height, weight, arms range, 20 yards, side shuffle, 300 meters, beep test), and with 11 parameters of situation efficiency in basketball (number of games, minutes per game, points per game, points, points total, steals, turnovers, assists, blocks, offensive rebounds, defensive rebounds, total rebounds). The results of the present study demonstrate that there is no significant relationship between initial measurements and parameters of situation efficiency. Results on this study are suggesting that improvement on several motoric abilities can implicate on parameters of situation efficiency. To our knowledge there is strong and significant relationship between initial and final motor measurements. As expected, the present study indicates that there is significant relationship between motor measurements and on parameters of situation efficiency.